The development of cryptocurrency in the modern economy of Kazakhstan: factors and indicators - Satmurzayev, A.A.; Berdimurat, A.; Zhadigerova, О.; Saparbayeva, S.S.; Akynov, D.M.; Ahmadiev, R. (BUKETOV BUSINESS REVIEW, 2024)
Object: Cryptocurrency and its significance for users living in Kazakhstan, the development of the economic and material condition of cryptocurrency holders. Methods: In the study correlation and regression analysis, literature analysis, methods of system analysis, statistics for the last 5 years were used. Findings: With the introduction of blockchain in the modern world, another prospect of earning money on cryptocurrency has appeared, for many people, cryptocurrency is applied as a method of payment, currency exchange, or in another way it is called Digital currency. In 2018, the rapid growth of Bitcoin / Etherium rapidly affected the consumer sector, based on foreign analysts who predicted the imminent collapse of the cryptocurrency, but the forecast did not materialize and today Bitcoin / Etherium are the most profitable and expensive assets in the 21st century. Conclusions: Despite the small percentage of people in Kazakhstan who actually invest in securities, stocks, dividends, etc., the material in this article will be able to motivate a large group of people to invest in crypto currency. This article also discusses how the “adoption” of the crypto currency in Kazakhstan will affect the current economy. How will a greater inflow of investments affect the well-being of the people, an increase in GDP, an increase in consumer demand, and an increase in economic benefits. Despite the insufficient group of people investing in crypto currency, they somehow encounter, contact in the modern world, feel its influence on the “response” of the global economy, thereby such a society helps to grow into a large entrepreneurial structure.